(untitled) (mathematica didactica, 2024)
In tertiary education didactics, proof comprehension has recently established itself as a growing research field. Although the models used there largely build upon each other, this article highlights inconsistencies in the consideration of different text levels. It merges the previous contributions into a unified model of proof comprehension, integrating current models from cognitive-psychological reading research. Using the example of different teaching and learning goals concerning proofs in school and university, the connectivity and the adaptivity of the unified model are demonstrated.